Efficacy and Safety of Glycopyrrolate/Formoterol Metered Dose Inhaler Formulated Using Co-Suspension Delivery Technology in Patients With COPD - Martinez, Fernando J; Rabe, Klaus F; Ferguson, Gary T; Fabbri, Leonardo M; Rennard, Stephen; Feldman, Gregory J; Sethi, Sanjay; Spangenthal, Selwyn; Gottschlich, Gregory M; Rodriguez-Roisin, Roberto; Arora, Samir; Siler, Thomas M; et al. (Chest, 2017)
Long-acting muscarinic antagonist (LAMA)/long-acting β -agonist (LABA) combinations are a treatment option for patients with COPD who continue to have symptoms despite treatment with a LAMA or a LABA alone. The Efficacy and Safety of PT003, PT005, and PT001 in Subjects with Moderate-to-Very Severe COPD (PINNACLE-1) (NCT01854645) and the Multi-Center Study to Assess the Efficacy and Safety of PT003, PT005, and PT001 in Subjects with Moderate-to-Very Severe COPD (PINNACLE-2) (NCT01854658) trials investigated the efficacy and safety of a novel glycopyrrolate [GP]/formoterol [FF] 18/9.6-μg (GFF) metered dose inhaler (MDI) formulated using the Co-Suspension Delivery Technology in patients with moderate-to-very severe COPD. These two phase III trials took place over 24 weeks and were randomized, double blind, and placebo controlled; 2,103 and 1,615 patients (40-80 years of age), respectively, were randomized. Patients received GFF MDI, GP MDI 18 μg, FF MDI 9.6 μg, or placebo MDI (all twice daily), or tiotropium 18 μg dry powder inhaler (once daily in PINNACLE-1 only [open-label active comparator]). Efficacy and safety were assessed. At week 24, differences in change from baseline in the morning predose trough FEV for GFF MDI vs placebo MDI, GP MDI, and FF MDI were 150 mL, 59 mL, and 64 mL in PINNACLE-1 (all P < .0001) and 103 mL, 54 mL, and 56 mL in PINNACLE-2 (all P < .001), respectively. There were no significant safety findings (incidence of adverse events was similar between treatment arms). We conclude that GFF MDI 18/9.6 μg demonstrated superiority over placebo and monocomponent MDIs and was well tolerated, thus providing an additional treatment option for patients with moderate-to-very severe COPD. ClinicalTrials.gov; No.: NCT01854645 and No. NCT01854658; URL: www.clinicaltrials.gov.